GENFIT: software for the analysis of small-angle X-ray and neutron scattering data of macromolecules in solution - Spinozzi, Francesco (International Union of Crystallography, 2014)
Many research topics in the fields of condensed matter and the life sciences are based on small-angle X-ray and neutron scattering techniques. With the current rapid progress in source brilliance and detector technology, high data fluxes of ever-increasing quality are produced. In order to exploit such a huge quantity of data and richness of information, wider and more sophisticated approaches to data analysis are needed. Presented here is GENFIT, a new software tool able to fit small-angle scattering data of randomly oriented macromolecular or nanosized systems according to a wide list of models, including form and structure factors. Batches of curves can be analysed simultaneously in terms of common fitting parameters or by expressing the model parameters via physical or phenomenological link functions. The models can also be combined, enabling the user to describe complex heterogeneous systems.